Technological Strategies in Brazil’s Manufacturing Industry: A Study Based on Innovative Activities - Carvalho, Enéas Gonçalves De [UNESP]; Melo, Tatiana Massaroli De [UNESP]; Gomes, Rogério [UNESP]; Guedes, Sebastião Neto Ribeiro [UNESP] (Universidade Estadual de Campinas, 2021)
The purpose of this article is to identify the technological strategies adopted in the Brazilian manufacturing industry. Technological strategies were analyzed for drafting of innovation and imitation product and process indicator, and, complementarily, by an additional indicator for organization and marketing innovations. The indicators were applied to 19 sectors of the Brazilian manufacturing industry (PINTEC, 2014) and to the counterparts of a set of selected European countries (CIS, 2016). For the purposes of analysis, the industrial sectors were grouped according to the criterion of technological intensity proposed by the OECD and the results compared with the sectoral innovation standards. The conclusions pointed out that the predominant strategies in the Brazilian industry are typically passive, in marked contrast to the active ones prevalent in developed countries.

O objetivo deste artigo é identificar as estratégias tecnológicas adotadas na indústria de transformação brasileira. As estratégias tecnológicas foram analisadas a partir da construção de indicadores de inovação e de imitação de produto e de processo e, complementarmente, de um indicador adicional para inovações organizacionais e de marketing. Os indicadores foram aplicados a 19 setores da indústria brasileira de transformação (PINTEC, 2014) e nas contrapartes de um conjunto de países europeus selecionados (CIS, 2016). Para efeitos de análise, os setores industriais foram agrupados segundo o critério de intensidade tecnológica proposto pela OCDE e os resultados confrontados com os padrões setoriais de inovação. Os resultados apontaram que as estratégias predominantes na indústria brasileira são tipicamente passivas, em claro contraste com as ativas prevalecentes nos países avançados.
Estratégias Tecnológicas na Indústria de transformação do Brasil: Um estudo a partir das atividades inovativas
Keywords: Strategies; Innovation strategies; Innovative activities; Manufacturing industry; Estratégias; Estratégias de Inovação; Atividades Inovativas; Indústria Transformação